Iowa Birdline update, December 19, 1990-January 2, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Emails for the Iowa Birdline update for December 19, 1990-January 2, 1991. Highlights of the updates include the continued presence of an Ivory Gull, a Townsend's Solitaire, a Black-legged Kittiwake, and Eurasian Tree Sparrows. Also of note were sightings of Red Crossbills, a Varied Thrush, a Northern Mockingbird, and 44 Great Horned Owls. Also included are the results from several Christmas bird counts from around the state. Epson - sheet feed/flatbed